Nonlocal Andreev reflection with Rashba spin-orbital interaction in a triple-quantum-dot ring - 彭菊 郁华玲 左芬 (Chinese physics B, 2010)
We theoretically studied the nonlocal Andreev reflection with Rashba spin-orbital interaction in a triple-quantumdot （QD） ring, which is introduced as Rashba spin-orbital interaction to act locally on one component quantum dot. It is found that the electronic current and spin current are sensitive to the systematic parameters. The interdot spin-flip term does not play a leading role in causing electronic and spin currents. Otherwise the spin precessing terra leads to shift of the peaks of the the spin-up and spin-down electronic currents in different directions and results in the spin current. Moreover, the spin-orbital interaction suppresses the nonlocal Andreev reflection, so we cannot obtain the pure spin current.